Stock Pricing Analysis of PT. LEN as Alternative Sources of Fund Through the Initial Public Offering (IPO) - Attamimi, Fahmy Helmy; Koesrindartoto, Deddy P; Sumirat, Erman (The Indonesian Journal of Business Administration, 2012)
PT. LEN is one of state owned companies (BUMN) in Indonesia which is engaged in technology industries. As one of state owned companies (BUMN) which enroll in strategic industries, PT. LEN has a very important role in supporting the growth of Indonesia’s development, PT. LEN’s business performance has successfully led PT. LEN as a trillion company. In 2011, the life cycle of this company has been projected from phase stability to phase growth. Nevertheless, one issue has arisen when the growth of the company is hampered by funding issue, especially the lack of capital to run the projects. The growth of revenues become unbalanced with working capital, especially liquid working capital (cash). The objective of the company is to Go Public with huge amount of capital which can support the business activities and also to strengthen the capital structure and the liquidity of assets. The sales revenue from some of its stocks is used as an alternative source of fund apart from bank loans. The fund is used to expand the company’s activities, to build the facility of developing system, and also to build fabrication workshop. The total amount of fund needed is 590 billion. During the IPO process, there are several things to be concerned, internally and externally. From the company’s internal perspective, several things to be be concerned are company’s feasibility studies in doing IPO. From the external perspective will affect investors’ interest to the company. This thesis uses discounted cash flow as a method to calculate the valuation of the company. This method is used to value stock’s price and the amount of stocks issued by PT. LEN for IP process so the price will be interesting to the investors. Other than to fulfill the needs of source funding, IPO process  is also one of the program to privatize the state owned companies in Indonesia which is included in BUMN’s Masterplan 2010-2014. Keywords: BUMN (state owned companies), Need of Funds, Initially Public Offering, Discounted Cash Flow.